Propit Sebagai Inovasi Model Pembelajaran Dalam Meningkatkan Aktivitas, Berpikir Kritis Pada Kelas Iv Sekolah Dasar - Amelianti; Mahmuddin (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is the low student activity and critical thinking skills. One effort to increase student activity, critical thinking skills, is through the use of the PROPIT learning model in grade 4 SDN Teluk Dalam 11 Banjarmasin. The purpose of this research is to increase the activity of teachers, students, critical thinking skills, and student learning outcomes. This research uses Classroom Action Research (CAR). The research subjects were 7 grade IV students at SDN Teluk Dalam 11 Banjarmasin for the academic year 2022/2023. The types of data in this study are qualitative and quantitative data. Qualitative data were obtained from observing the activities of teachers, students, and critical thinking skills questionnaires. Quantitative data were obtained from individual written test measurement techniques. The results showed that teacher activity at meetings I to IV increased from a score of 23 to a score of 28. Student activity at meetings I to IV increased from 57.2% to 100%. Critical Thinking Skills at meetings I to IV increased from 42.9% to 85.8%. So that it has an impact on cognitive aspects of learning outcomes from 57.2% to 100%. Affective learning outcomes at meetings 1 to 4 increased from 42.9% to 100%. Psychomotor learning outcomes at meetings 1 to 4 increased from 57.2% to 100% classically.